2003
DOI: 10.1081/jas-120017207
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Sensitivity and Asthma Severity at an Inner City Asthma Center

Abstract: The objective of this study was to examine the relationship of allergen sensitivity to asthma symptoms among inner-city asthmatics seen at our Brooklyn, NY, asthma center. We hypothesized that asthma severity would increase for adults and children with increased cockroach and dust mite allergen sensitivity. Data were gathered from retrospective chart review for all patients who were treated at the center with a diagnosis of asthma and had undergone skin-prick testing (SPT) for allergen sensitivity during 1998 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
2
32
1
Order By: Relevance
“…The investigations that have been reported were at single sites and tended to have small sample sizes. 5,6,9 In a study of patients being evaluated by radioallergosorbent testing in New York City, asthmatics were more likely than non-asthmatics to be hypersensitized to cat dander or dust mites (D. farinae) and to Deuteromycetes molds (Alternaria tenuis, Aspergillus fumigatus, and Cladosporium herbarum), whereas pollen (tree, grass, ragweed) hypersensitivity was not independently associated with asthma. 9 Although cat dander was excluded from another New York City study of allergic sensitization, 6 most (83%) of the 29 adults with asthma had a positive skin prick test to at least one of 7 common allergens or allergen mixtures: ragweed, grasses, dust mite (Dermatophagoides pteronyssinus and D. farinae), and trees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The investigations that have been reported were at single sites and tended to have small sample sizes. 5,6,9 In a study of patients being evaluated by radioallergosorbent testing in New York City, asthmatics were more likely than non-asthmatics to be hypersensitized to cat dander or dust mites (D. farinae) and to Deuteromycetes molds (Alternaria tenuis, Aspergillus fumigatus, and Cladosporium herbarum), whereas pollen (tree, grass, ragweed) hypersensitivity was not independently associated with asthma. 9 Although cat dander was excluded from another New York City study of allergic sensitization, 6 most (83%) of the 29 adults with asthma had a positive skin prick test to at least one of 7 common allergens or allergen mixtures: ragweed, grasses, dust mite (Dermatophagoides pteronyssinus and D. farinae), and trees.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although cat dander was excluded from another New York City study of allergic sensitization, 6 most (83%) of the 29 adults with asthma had a positive skin prick test to at least one of 7 common allergens or allergen mixtures: ragweed, grasses, dust mite (Dermatophagoides pteronyssinus and D. farinae), and trees. 6 At the Portland, OR, site in the European Community respiratory health survey (ECRHS) studies, 74% of the 39 participants with asthma were sensitized to at least one of 9 common allergens, the most frequent sensitizations being to timothy grass, D. pteronyssinus, birch, A. alternata, and cat. 5 Thus, studies in the United States have consistently observed a high prevalence of atopy among adult asthmatics, with the distribution of specific allergen sensitivities varying between sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have focused on the most common indoor allergens in children living in tropical climates, which contributes to respiratory infections as they are suspected triggers of asthma exacerbations. 5,9,[11][12][13][14] Therefore, we conducted a study to examine the correlation between sensitization to common indoor allergens and the frequency of asthma exacerbations. We also investigated the correlation between mean wheal diameters of each allergen and the frequency of asthma exacerbations.…”
mentioning
confidence: 99%